Direct Instantaneous Power Control of Three-level Grid-connected - Yang Yong (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Power electronic grid-connected inverters are widely applied as grid interface in renewable energy sources. This paper presents direct instantaneous power control of a three-phase three-level Neutral Point Clamped (NPC) grid-connected inverter in photovoltaic generation systems. The system consists of a PV array, DC/DC converter, three-level NPC LC filter and the grid. In order to achieve maximum power point  tracking (MPPT), an adaptive perturb and observe MPPT is used. For balancing the neutral point (NP) voltage, the control scheme through proportional integral (PI) control according to  the direction of the NP current based on redundant vector selection is used. Direct instantaneous power control is developed in a rotating synchronous dq reference frame with space vector modulation with improved operation performance study of the positive sequence detector (PSD) plus a synchronous a synchronous reference frame phase-locked loop (PLL) as the synchronization method. The performance of the proposed method is investigated by a grid-connected photovoltaic system with a nominal power of 12kW. The feasibility of the proposed method is verified through experimental results, showing good steady-state and dynamic performance.